The Impact of Integrated Public Transport Modes on Environmental Sustainability in Batam, Indonesia - Sugito, Ery; Safitri, Khoerun Nisa; Syaputra, Buang; Qilbi, Fath Ainun (Institut Transportasi dan Logistik Trisakti, 2026)
Efficient urban mobility is a fundamental element in supporting economic growth and enhancing the quality of life for the population. The integration of transport modes serves as a viable solution to address issues such as traffic congestion, limited accessibility, and travel inefficiency in urban areas. This study analyses the impact of transport mode integration on urban mobility from three key dimensions: physical, operational, and policy-based. The research is particularly relevant given the growing demand for efficient and sustainable public transportation in developing cities. Employing Partial Least Squares Structural Equation Modelling and primary data collected from public transport users, the findings indicate that all three dimensions of integration significantly influence urban mobility, with operational integration emerging as the most dominant factor. Furthermore, urban mobility was found to have a positive impact on reducing environmental harm. The research model satisfies the criteria for validity and reliability, with a Goodness of Fit (GoF) value of 0.607. The findings recommend the acceleration of integrated infrastructure development, the optimisation of technology-based operational management, and the harmonisation of transport policies to create a more sustainable transport system. Future studies may consider extending the model by incorporating mediating variables such as green technology and broadening the scope of analysis to include socio-economic dimensions